Negotiating Pure Ideas and Religious Thought in Qur’anic Exegesis: An Analysis of Muḥammad Saʿīd al-ʿAshmāwī’s Concept of Homosexuality Verses - Udin Safala (QOF, 2025)
This study examines Muḥammad Saʿīd al-ʿAshmāwī’s conceptual approach to interpreting Qur’anic verses concerning homosexuality, emphasizing the distinction between al-fikr al-ṣāfī (pure ideas) and al-fikr al-dīnī (religious thought). Al-ʿAshmāwī asserts that pure ideas are transcendent and objective, whereas religious thought constitutes human interpretation influenced by social, historical, and cultural contexts. The study aims to explore how this framework enables exegesis that preserves normative principles while remaining responsive to contemporary social, ethical, and legal dynamics. Employing a qualitative methodology through literature review, the analysis is both thematic-categorical and epistemological, examining relevant Qur’anic verses and al-ʿAshmāwī’s works. Findings indicate that his approach foregrounds the moral, ethical, and social essence of revelation, treating legal prescriptions as contextually constructed by humans. By integrating classical and modern hermeneutics with local and global perspectives, this method ensures interpretations remain relevant to issues of justice, human dignity, and contemporary social dynamics. The study contributes to the development of a transformative exegetical framework that bridges transcendent principles and human interpretive needs in a humanistic, critical, and practical manner, offering a methodological foundation for contemporary Qur’anic studies.